Determining demographic profiles and tourists' motives for visiting Langkawi Island - Hamdan, Nurul Shahida; Yusof, Aminuddin (IKRAM Education, 2014)
The purpose of the study is to address the profile of tourists visiting Langkawi and determine the motives of tourists visiting Langkawi. Using a quantitative research approach, data were collected from 340 respondents visiting Langkawi using the Leisure Motivation Scale (LMS) [1]. Data were analysed using descriptive statistics and t-test. The results showed that there were two kinds of tourists visiting Langkawi: sports tourists and non – sports tourists. The majority of sports tourists (72.9%) from the age of 22 up till 28 years of age was more interested in sports tourism and was found to be losing their interest in sports tourism at around the age of 28 to 33 years of age. Results also showed that there are no significant differences in terms of motives between sports tourists and non-sports tourists traveling to Langkawi. The information obtained from this study can be used by people in the sports tourism industry to implement it into their marketing segmentation by targeting the right type of tourist coming to Langkawi.